Вегетативне розмноження видів роду Viburnum L. - Demchenko, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The results of investigations on vegetative reproduction of 11 species and 5 form of Viburnum L. are given. The most effective method of vegetative reproduction is taking green cuttings with the use of heteroauxin as rhizogenesis stimulator.